2023
DOI: 10.3390/v15020437
|View full text |Cite
|
Sign up to set email alerts
|

Ecological, Genetic, and Phylogenetic Aspects of YFV 2017–2019 Spread in Rio de Janeiro State

Abstract: In Brazil, a yellow fever (YF) outbreak was reported in areas considered YF-free for decades. The low vaccination coverage and the increasing forest fragmentation, with the wide distribution of vector mosquitoes, have been related to yellow fever virus (YFV) transmission beyond endemic areas since 2016. Aiming to elucidate the molecular and phylogenetic aspects of YFV spread on a local scale, we generated 43 new YFV genomes sampled from humans, non-human primates (NHP), and primarily, mosquitoes from highly he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Several factors underpin the reemergence of YFV in Southern Brazil, including inadequate vaccination coverage; the abundance of sylvatic vectors and NHP hosts; favorable climatic conditions; the emergence of new virus lineages; and the movement of infected humans and NHPs into new areas sharing these conducive conditions [ 6 ]. In addition, during the recent YF outbreaks in Brazil, the observed temporal and geographical patterns of YFV dispersion indicated the important role of vectors in YFV movement [ 7 , 8 ]. From late 2016 to 2018, Brazil experienced a dramatic shift in YF epidemiology, with a major outbreak in the Southeast region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors underpin the reemergence of YFV in Southern Brazil, including inadequate vaccination coverage; the abundance of sylvatic vectors and NHP hosts; favorable climatic conditions; the emergence of new virus lineages; and the movement of infected humans and NHPs into new areas sharing these conducive conditions [ 6 ]. In addition, during the recent YF outbreaks in Brazil, the observed temporal and geographical patterns of YFV dispersion indicated the important role of vectors in YFV movement [ 7 , 8 ]. From late 2016 to 2018, Brazil experienced a dramatic shift in YF epidemiology, with a major outbreak in the Southeast region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the importance of natural barriers, such as preserved native vegetation [17,24], mountain ranges like the Serra do Mar [29], and highly anthropized and modified areas such as agricultural areas and large urban centers [17,49], to limit virus propagation by restricting the movement of vector mosquitoes. The results obtained in this study corroborate these findings.…”
Section: Vector Abundance Extrapolation Corridors and Risk Areas For ...mentioning
confidence: 99%
“…The largest and most recent outbreak of WYF recorded in Brazil occurred between 2016 and 2021 [9,15,27] in the southeast and south regions of the country [4,[27][28][29]. In these regions, Hg.…”
Section: Introductionmentioning
confidence: 99%